All-inorganic GaAs / perovskite series laminated cell with carbon material as hole transport and conductive multifunctional intermediate composite layer and preparation method of all-inorganic GaAs / perovskite series laminated cell
By using carbon material as a multifunctional intermediate composite layer in GaAs/perovskite tandem batteries, the problems of complex structure, high cost and poor stability are solved, and the battery structure is simplified, reducing costs and improving stability are achieved.
Patent Information
- Application Number
- CN202411540713.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing GaAs/perovskite tandem batteries have complex structures, high cost and poor stability, making it difficult to break through the limit efficiency.
Carbon materials are used as a multifunctional intermediate composite layer for hole transport and conduction, simplifying the battery structure and reducing costs, and using all-inorganic materials to improve stability.
The battery structure is simplified, production costs are reduced, and the battery stability is significantly improved, and battery performance is optimized.
Smart Images

Figure CN119421599A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of GaAs series stacked solar cells, and specifically relates to a fully inorganic GaAs / perovskite series stacked cell with a carbon material as a hole transport and conductive multifunctional intermediate composite layer and a preparation method thereof. Background Art
[0002] In recent years, GaAs (Gallium Arsenide) solar cells have been widely used due to their direct band gap, excellent photoelectric conversion efficiency and radiation resistance. According to the Shockley-Queisser model, the photoelectric conversion efficiency of a single-junction GaAs solar cell can reach 30%.
[0003] In order to break through the limit efficiency of GaAs solar cells, GaAs / perovskite tandem cells have received widespread attention. Perovskite solar cells have the advantages of simple preparation process and low cost, and their bandgap width range can make it a top cell of a multi-junction cell. The patent with application number 202210046762.X discloses a four-terminal stacked perovskite solar cell and its preparation method. The tandem cell structure used in the patent is a four-terminal type, and two complete cell structures need to be prepared and pressed together by pressure, which will inevitably make the process complicated and the cost significantly increased. The application with application number 202210675836.6 discloses a perovskite / GaAs two-terminal mechanical stacked solar cell with a metal grid interconnection layer. The application uses a metal grid as the intermediate interconnection conductive layer between the GaAs bottom cell and the perovskite top cell, which is costly and increases the process flow. In addition, its top cell uses an organic perovskite absorption layer with poor stability. Summary of the invention
[0004] In order to overcome the above problems of complex structure, high cost and poor stability, the present invention provides an all-inorganic GaAs / perovskite tandem stacked cell with carbon material as hole transport and conductive multifunctional intermediate composite layer and its preparation method. The present invention can simplify the cell structure and reduce the cost by using carbon material as the multifunctional composite layer for hole transport of the bottom cell and the conductive interconnection of the middle cell.
[0005] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0006] An all-inorganic GaAs / perovskite tandem stacked cell with carbon material as a hole transport and conductive multifunctional intermediate composite layer, comprising, from bottom to top, a back electrode, a GaAs substrate layer, a carbon material layer, an inorganic perovskite top cell layer, a front ARC, and a front electrode; wherein the carbon material is a composite functional layer serving as hole transport of the GaAs bottom cell and intermediate interconnection and conductivity between the bottom cell and the top cell, and the inorganic perovskite top cell layer comprises, from bottom to top, an electron transport layer, a perovskite absorption layer, and a hole transport layer;
[0007] The front electrodes are arranged at both ends of the hole transport layer in the inorganic perovskite top battery layer, and the front ARC is arranged on the hole transport layer in the inorganic perovskite top battery layer and contacts the front electrodes at both ends; the electron transport layer is arranged on the carbon material layer.
[0008] The back electrode is an Au electrode; the front electrode is an Ag electrode.
[0009] A method for preparing an all-inorganic GaAs / perovskite tandem cell with a carbon material as a hole transport and conductive intermediate composite functional layer comprises the following steps:
[0010] 1) evaporating a back electrode on one surface of a GaAs substrate, annealing to form an ohmic contact, and then preparing a carbon material layer on the other surface of the GaAs substrate to obtain a GaAs bottom cell;
[0011] 2) preparing an electron transport layer on the surface of the carbon material layer;
[0012] 3) preparing an inorganic perovskite precursor into a solution, spin coating the solution on the surface of the electron transport layer using an anti-solvent method, and annealing the solution at a high temperature to obtain a perovskite absorption layer;
[0013] 4) preparing a hole transport layer on the surface of the perovskite absorption layer;
[0014] 5) vapor-depositing front electrodes at both ends of the hole transport layer, and vapor-depositing an anti-reflection coating on the hole transport layer not covered by the front electrode, to obtain an all-inorganic GaAs / perovskite tandem cell with carbon material as the hole transport and conductive intermediate composite functional layer.
[0015] In step 1), the back electrode is an Au electrode, the thickness of the Au electrode is 100-120 nm, the annealing temperature is 300-330° C., and the annealing time is 15-30 s.
[0016] The carbon material is one or more of carbon nanotubes, graphene, carbon fibers, and carbon quantum dots;
[0017] The carbon material layer is obtained by preparing a film by suction filtration of the carbon material or by wet transfer of the material, and has a thickness of 100 to 200 nm.
[0018] The electron transport layer in step 2) is one or more of TiO2, SnO2, C60, BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) or PCBM (benzo[c][1,2,5]thiadiazole-4,7-diimide).
[0019] The electron transport layer is prepared by magnetron sputtering, and the preparation conditions are: power of 60-120W, vacuum degree of 0.4-0.7Pa, and sputtering time of 1-3min.
[0020] The inorganic perovskite in step 3) is one or more of CsPbI3, CsPbBr3, and CsSnI3;
[0021] The precursor is CsI, PbI2, CsBr, PbBr2 and / or SnI2, and the solvent in the precursor solution is DMF and DMSO, with a volume ratio of (3-5):1.
[0022] The concentration of the precursor solution is 0.5-1.2M.
[0023] The precursor solution is prepared by stirring the precursor and the solvent; the stirring temperature is 50 to 90° C. and the stirring time is 8 to 12 hours.
[0024] During the preparation of the perovskite absorption layer, the substrate is preheated to 50-80°C before spin coating the precursor, and the preheating time is 3-5 minutes; the rotation speed of the spin coating precursor is 2000-3000rpm, and the time is 20-60 seconds; the time for adding the anti-solvent is 10-15 seconds before the end of the rotation.
[0025] The temperature of high temperature annealing is 200-340°C and the time is 10-30 minutes.
[0026] The anti-solvent can be chlorobenzene, toluene, ethyl acetate, etc.
[0027] The volume ratio of the antisolvent to the spin-coated perovskite precursor solution is 10 to 50:10.
[0028] The hole transport layer described in step 4) is PEDOT (polyethylene dioxythiophene), Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), P3HT (poly 3-hexylthiophene), 2PACz (2-[(2-chlorophenyl)(phenyl)amino]ethyl benzoate), etc.
[0029] The hole transport layer is prepared by spin coating and then annealed; the spin speed is 4000-6000 rpm, the time is 30-60s, the annealing temperature is 100-150°C, and the annealing time is 10-20min.
[0030] The material of the hole transport layer is prepared into a solution, the solvent in the solution is isopropanol, and the concentration is 0.5-1.5 mg / mL; the thickness of the hole transport layer is 50-150 nm.
[0031] In step 5), the ARC anti-reflective coating is ITO, WO3, PMDS, etc.
[0032] The thickness of the ARC is 10 to 30 nm, and the thickness of the Ag electrode is 100 to 120 nm.
[0033] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0034] The GaAs bottom cell in the battery structure of the present invention adopts a heterojunction cell, which reduces the cost compared with a homojunction cell. The use of carbon material as a composite functional layer reduces the intermediate conductive layer required for traditional series cells, which can effectively reduce costs and optimize the battery structure. In addition, the all-inorganic GaAs / perovskite cell can significantly improve stability and other advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the structure of the all-inorganic GaAs / perovskite tandem stacked cell in which the carbon material of the present invention is used as a hole transport and conductive multifunctional intermediate composite layer; 1-back electrode, 2-GaAs substrate layer, 3-carbon material layer, 4-electron transport layer, 5-perovskite absorption layer, 6-hole transport layer, 9-front ARC, 7-front electrode; 8-inorganic perovskite top cell layer, the inorganic perovskite top cell layer includes, from bottom to top, an electron transport layer 4, a perovskite absorption layer 5, and a hole transport layer 6;
[0036] Figure 2 This is a flow chart for preparing an all-inorganic GaAs / perovskite tandem cell structure using graphene as a hole transport and conductive multifunctional intermediate composite layer in Example 2. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0038] An all-inorganic GaAs / perovskite tandem stacked cell with carbon material as hole transport and conductive multifunctional intermediate composite layer, the structural schematic diagram of which is shown in the figure Figure 1As shown, from bottom to top, it includes a back electrode 1, a GaAs substrate layer 2, a carbon material layer 3, an inorganic perovskite top cell layer 8, a front ARC 9, and a front electrode 7; wherein the carbon material is a composite functional layer serving as hole transport for the GaAs bottom cell and intermediate interconnection and conductivity between the bottom cell and the top cell, and the inorganic perovskite top cell layer 8 includes, from bottom to top, an electron transport layer 4, a perovskite absorption layer 5, and a hole transport layer 6.
[0039] The front electrode 7 is arranged at both ends of the hole transport layer 6 in the inorganic perovskite top battery layer, and the front ARC 9 is arranged on the hole transport layer 6 in the inorganic perovskite top battery layer and contacts the front electrodes at both ends; the electron transport layer 4 is arranged on the carbon material layer 3.
[0040] The back electrode is an Au electrode; the front electrode is an Ag electrode.
[0041] Example 1
[0042] A method for preparing an all-inorganic GaAs / perovskite tandem stacked cell with a carbon material as a hole transport and conductive multifunctional intermediate composite layer, comprising the following steps:
[0043] 1) an Au back electrode (the thickness of the Au electrode is 120 nm) is evaporated on one surface of a GaAs substrate, and annealed at a temperature of 330° C. for 30 seconds to form an ohmic contact, and then a carbon nanotube layer is prepared on the surface of the clean GaAs substrate by a filtration technique (the thickness of the nanotube layer is 100 nm; the carbon nanotubes are dispersed in water, and then the carbon nanotube layer is prepared by filtration) to obtain a GaAs bottom cell;
[0044] 2) preparing a perovskite top cell on the surface of the GaAs bottom cell prepared in step 1), and preparing a layer of TiO2 electron transport layer material on the nanotube layer by magnetron sputtering, with a power of 60W, a vacuum degree of 0.47Pa, and a sputtering time of 2min;
[0045] 3) Weigh 0.5g CsI and 0.8865g PbI and stir and dissolve them in 3ml of a mixed solvent of DMF and DMSO (the volume ratio of DMF:DMSO is 4:1), stir at 70°C for 8h, and obtain a precursor solution with a concentration of 0.65M; preheat the substrate in step 2) at 50°C for 3min, put it into a spin coating device, and spin coat at a speed of 3000rpm for 30s (the amount of the precursor solution spin-coated is 10μL), and 15s before the end of the rotation, drop 50μL of chlorobenzene anti-solvent, and then perform high-temperature annealing at 340°C for 10min, and then rapidly cool to obtain a perovskite absorption layer;
[0046] 4) Prepare a layer of 2PACz hole transport layer material on the perovskite absorption layer by spin coating (the solvent in the 2PACz solution is isopropanol with a concentration of 1 mg / mL and an addition amount of 10 μL), the rotation speed is 2000 rpm, the time is 30 s, and annealing is performed after spin coating, the annealing temperature is 100° C., and the annealing time is 10 min;
[0047] 5) A layer of ARC (WO3) and Ag electrode are evaporated on the surface of the hole transport layer, the ARC is located in the area not covered by the Ag electrode, the Ag electrodes are located at both ends, the thickness of the ARC is 30nm, and the thickness of the Ag electrode is 120nm, so as to obtain a fully inorganic / perovskite tandem battery with carbon nanotubes as hole transport@conductive intermediate composite functional layers.
[0048] Example 2
[0049] An all-inorganic GaAs / perovskite tandem cell structure with graphene material as a hole transport and conductive intermediate composite functional layer and a preparation method thereof, comprising the following steps:
[0050] 1) an Au back electrode is evaporated on one surface of a GaAs substrate, the thickness of the Au electrode is 120 nm, and annealed at a temperature of 330° C. for 30 seconds to form an ohmic contact, and then a graphene composite functional layer (the thickness of the graphene layer is 100 nm) is prepared on the surface of a clean GaAs substrate by wet transfer technology to obtain a GaAs bottom cell;
[0051] 2) preparing a perovskite top cell on the surface of the GaAs bottom cell prepared in step 1), and preparing a layer of SnO2 electron transport layer material by magnetron sputtering, with a power of 80 W, a vacuum degree of 0.47 Pa, and a sputtering time of 2.5 min;
[0052] 3) Weigh 0.5g CsI and 0.8865g PbI and dissolve them in 3ml DMF and DMSO solvent (the volume ratio of DMF:DMSO is 4:1), stir at 70°C for 8h, and obtain a precursor solution with a concentration of 0.65M; preheat the substrate in step 2) at 80°C for 5min, put it into a spin coating device, and spin coat at a speed of 3000rpm for 30s. 15s before the end of the rotation, dropwise add chlorobenzene antisolvent, perform high temperature annealing at 300°C for 10min, and then rapidly cool to obtain a perovskite absorption layer;
[0053] 4) preparing a layer of PEDOT hole transport layer material on the perovskite absorption layer by spin coating (the solvent of the PEDOT solution is isopropanol, with a volume fraction of 50%), with a rotation speed of 6000 rpm, a time of 30 s, an annealing temperature of 140° C., and an annealing time of 10 min;
[0054] 5) A layer of ARC (WO3) and an Ag electrode are evaporated on the surface of the hole transport layer, wherein the ARC is located on the hole transport layer not covered by the Ag electrode and the Ag electrodes are located at both ends. The thickness of the ARC is 20 nm and the thickness of the Ag electrode is 120 nm. Thus, a fully inorganic / perovskite tandem stacked cell with graphene as a hole transport@conductive intermediate composite functional layer can be obtained.
[0055] The preparation flow chart of this embodiment is as follows Figure 2 shown.
[0056] Comparative Example 1
[0057] The difference between Comparative Example 1 and Examples 1 and 2 is that the prepared battery is a GaAs / carbon nanotube single junction battery, and no stacking operation with a perovskite battery is performed.
[0058] The comparison of the device parameters of the solar cell prepared in Example 1 and the solar cell prepared in Comparative Example 1 is shown in Table 1.
[0059] Table 1 Performance parameters of solar cell devices prepared in Example 1 and Comparative Example 1
[0060] Parameters / Samples Example 1 Comparative Example 1 <![CDATA[Jsc(mA / cm 2 )]]> 12.26 8.35 V(v) 1.26 0.71 PCE(%) 9.42 3.56
[0061] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. An all-inorganic GaAs / perovskite tandem stacked cell with carbon material as a multifunctional intermediate composite layer for hole transport and conduction, characterized in that: From bottom to top, it includes back electrode, GaAs substrate layer, carbon material layer, inorganic perovskite top cell layer, front ARC, and front electrode; The carbon material is a composite functional layer that serves as hole transport for the GaAs bottom cell and as an intermediate interconnection and conductivity between the bottom cell and the top cell. The inorganic perovskite top cell layer includes an electron transport layer, a perovskite absorption layer, and a hole transport layer from bottom to top. The front electrodes are arranged at both ends of the hole transport layer in the inorganic perovskite top battery layer, and the front ARC is arranged on the hole transport layer in the inorganic perovskite top battery layer and contacts the front electrodes at both ends; the electron transport layer is arranged on the carbon material layer.
2. According to claim 1, the all-inorganic GaAs / perovskite tandem stacked cell with the carbon material as the hole transport and conductive multifunctional intermediate composite layer is characterized in that: The back electrode is an Au electrode; the front electrode is an Ag electrode.
3. A method for preparing an all-inorganic GaAs / perovskite tandem cell using the carbon material as a hole transport and conductive intermediate composite functional layer according to claim 1 or 2, characterized in that: The following steps are involved: 1) A back electrode is evaporated on one surface of a GaAs substrate, annealed to form an ohmic contact, and then a carbon material layer is prepared on the other surface of the GaAs substrate to obtain a GaAs bottom cell; 2) preparing an electron transport layer on the surface of the carbon material layer; 3) preparing an inorganic perovskite precursor into a solution, spin coating the solution on the surface of the electron transport layer using an anti-solvent method, and annealing the solution at a high temperature to obtain a perovskite absorption layer; 4) preparing a hole transport layer on the surface of the perovskite absorption layer; 5) The front electrodes are evaporated at both ends of the hole transport layer, and the anti-reflection coating ARC is evaporated on the hole transport layer not covered by the front electrode to obtain an all-inorganic GaAs / perovskite tandem cell with carbon material as the hole transport and conductive intermediate composite functional layer.
4. The method for preparing an all-inorganic GaAs / perovskite tandem cell using the carbon material as a hole transport and conductive intermediate composite functional layer according to claim 3, characterized in that: The carbon material in step 1) is one or more of carbon nanotubes, graphene, carbon fibers, and carbon quantum dots; The carbon material layer is obtained by preparing a film by suction filtration or wet transfer of the carbon material, and the thickness of the carbon material layer is 100-200nm.
5. The method for preparing the all-inorganic GaAs / perovskite tandem cell with the carbon material as the hole transport and conductive intermediate composite functional layer according to claim 3, characterized in that: The back electrode in step 1) is an Au electrode, and the thickness of the Au electrode is 100-120 nm; the annealing temperature in step 1) is 300-330° C., and the annealing time is 15-30 s; The electron transport layer in step 2) is TiO2, SnO2, C60, BCP or PCBM; The electron transport layer is prepared by magnetron sputtering, and the preparation conditions are: power of 60-120W, vacuum degree of 0.4-0.7Pa, and sputtering time of 1-3min.
6. The method for preparing the all-inorganic GaAs / perovskite tandem cell with the carbon material as the hole transport and conductive intermediate composite functional layer according to claim 3, characterized in that: The inorganic perovskite in step 3) is one or more of CsPbI3, CsPbBr3, and CsSnI3; In step 3), the perovskite precursor is CsI, PbI2, CsBr, PbBr2 and / or SnI2; after the precursor is prepared into a solution, the solvent in the solution is DMF and DMSO, and the volume ratio is (3-5): 1; When the inorganic perovskite is CsPbI3, the perovskite precursor is CsI and PbI2, When the inorganic perovskite is CsPbBr3, the perovskite precursors are CsBr and PbBr2; When the inorganic perovskite is CsSnI3, the perovskite precursors are CsI and SnI2; The concentration of the precursor solution is 0.5-1.2M.
7. The method for preparing the all-inorganic GaAs / perovskite tandem cell with the carbon material as the hole transport and conductive intermediate composite functional layer according to claim 3, characterized in that: In the preparation process of the perovskite absorption layer, the substrate is preheated to 50-80°C before spin coating the precursor solution, and the preheating time is 3-5 minutes; the rotation speed of the spin coating precursor is 2000-3000rpm, and the time is 20-60 seconds; the time of dripping the anti-solvent in the anti-solvent method is 10-15 seconds before the end of the rotation; Step 3) the temperature of medium-high temperature annealing is 200-340°C and the time is 10-30min; The anti-solvent is one or more of chlorobenzene, toluene and ethyl acetate.
8. The method for preparing the all-inorganic GaAs / perovskite tandem cell with the carbon material as the hole transport and conductive intermediate composite functional layer according to claim 3, characterized in that: The hole transport layer in step 4) is one or more of PEDOT, Spiro-OMeTAD, P3HT, and 2PACz; The hole transport layer is prepared by preparing a solution of the hole transport layer material, spin coating, and then annealing; the spin coating rotation speed is 4000-6000 rpm, the time is 30-60s, the annealing temperature is 100-150°C, and the annealing time is 10-20min; the solvent in the solution is isopropanol, and the concentration is 0.5-1.5 mg / mL; the thickness of the hole transport layer is 50-150 nm.
9. The method for preparing the all-inorganic GaAs / perovskite tandem cell with the carbon material as the hole transport and conductive intermediate composite functional layer according to claim 3, characterized in that: In step 5), the ARC anti-reflective coating is ITO, WO3, or PMDS; The thickness of the ARC is 10 to 30 nm, and the thickness of the front electrode Ag electrode is 100 to 120 nm.
Citation Information
Patent Citations
A four-terminal stacked perovskite solar cell and its fabrication method
CN114335216B
Perovskite / GaAs two-end mechanical laminated solar cell with metal grid interconnection layer
CN115000057A
All-inorganic perovskite solar cell and preparation method thereof
CN109473554A
Non-temperature-resistant flexible perovskite solar cell for realizing high-temperature annealing and preparation method of non-temperature-resistant flexible perovskite solar cell
CN118215308A
Perovskite-carbon nanotube silicon heterojunction two-end type laminated cell and preparation method thereof
CN118215314A